Returns to Schooling among Immigrants in Spain: A Quantile Regression Approach - Santiago Budría; Pablo Swedberg; Marlene Fonseca (Institute for the Study of Labor (IZA), 2016)
This paper explores the impact of educational attainment on immigrant earnings in Spain using a Quantile Regression approach. Most of the previous research on the impact schooling on earnings has focused on the mean effect neglecting the discrepancies that arise from unobserved heterogeneity. This paper uses the Spanish National Immigrant Survey (NIS), a large-scale immigration survey published by the Spanish National Statistics Institute in 2008. We find that the return to higher education is on average roughly 17%. Interestingly, the impact is twice as strong (20.7%) for immigrants at the top two quintile(s) of the conditional earnings distribution than for those at the bottom of the distribution (10%). This result suggests that the benefits derived from higher education are particularly relevant for individuals with stronger unobserved abilities and marketable skills. By contrast, individuals in the middle and particularly lower quintiles fail to reap a significant return. The large degree of heterogeneity for the returns to schooling found in our research suggests that higher education may be less effective among specific population groups.
Keywords: C29; D31; I21; 330; returns to education; quantile regression; wage inequality